STOMATAL CONDUCTANCE OF DUKU (LANSIUM DOMESTICUM CORR.) IN RESPONSE TO INUNDATION - Mapegau M.; Hayati I.; Nusifera S.; Ichwan B.; Irianto I.; Nasamsir N. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
The study aimed at evaluating the stomatal conductance reaction in several duku accessions to inundation conditions. This study was conducted in the Experiment Station of the Faculty of Agriculture, Jambi University, Mendalo Indah Village, Muaro Jambi Regency. The research was carried out simultaneously or in series in two groups. Group I had no inundation of planting media or 100% field capacity (FC) and Group II had inundation (150% FC) of planting media using a Completely Randomized Design (CRD) with 3 replications. One variety and tree accessions of Jambi duku tested for their response to inundation in this study were: Duku Variety Kumpeh (DVK-01), Duku Selat Accession (DSA-1), duku Danau Lamo Accession (DLA-2, and Duku Senaning accession (DSA-3). The observed variables include Relative Water Content (RWC), Stomatal Conductance (SC), and Photosynthetic Rate (PR). The results showed that inundation at the level of 150% field capacity (FC) affected all observed variables. There was a decrease in RWC, SC, and PR values in DSA-1, DLA-2, and DSA-3 compared with no inundation (100% FC). DVK-01 (duku variety Kumpeh) showed relatively no decrease in RWC, SC, and PR values. At the inundation level of 150% FC, RWC, SC, and PR values were comparatively the same in all tested accessions. The adaptation mechanism of the three accessions tested in response to inundation was seemingly through a decrease in stomatal conductance, while the Kumpeh variety (DVK-01) by maintaining root permeability. The information obtained from this study can be used for further evaluation of the physiological traits of duku in the future.